2020
DOI: 10.5603/cj.a2020.0071
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and reproducibility of optical flow ratio for functional evaluation of coronary stenosis in a prospective series

Abstract: Background: Evaluating prospectively the feasibility, accuracy and reproducibility of optical flow ratio (OFR), a novel method of computational physiology based on optical coherence tomography (OCT). Methods and results: Sixty consecutive patients (76 vessels) underwent prospectively OCT, angio graphybased quantitative flow ratio (QFR) and fractional flow ratio (FFR). OFR was computed offline in a central corelab by analysts blinded to FFR. OFR was feasible in 98.7% of the lesions and showed excellent agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…When comparing OCT-FFR to OCT-based machine learning-FFR for the patients in this study, the OCT-based machine learning-FFR (r = 0.853) had better correlation compared with CFD-based OCT FFR (r = 0.712) on the same set of patients. In addition, even considering different patient population and vessel characteristics, the OCT-based machine learning-FFR demonstrated a better or comparative result to the wire-based FFR results than did OCT-FFR (r = 0.83) 13 or CT-FFR (r = 0.82) 12 . These findings suggested that the OCT-based machine learning-FFR results could be used to predict FFR as an alternative method to both CT-FFR and OCT-FFR.…”
Section: Discussionmentioning
confidence: 87%
“…When comparing OCT-FFR to OCT-based machine learning-FFR for the patients in this study, the OCT-based machine learning-FFR (r = 0.853) had better correlation compared with CFD-based OCT FFR (r = 0.712) on the same set of patients. In addition, even considering different patient population and vessel characteristics, the OCT-based machine learning-FFR demonstrated a better or comparative result to the wire-based FFR results than did OCT-FFR (r = 0.83) 13 or CT-FFR (r = 0.82) 12 . These findings suggested that the OCT-based machine learning-FFR results could be used to predict FFR as an alternative method to both CT-FFR and OCT-FFR.…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, the benefit of revascularization in asymptomatic patients is unclear and difficult to justify after ISCHEMIA for prognostic reasons. All these questions will require specific answers in the future, always keeping in mind that coronary interventions are moving toward physiology guidance and precision medicine [22], rather than relying on the haziness of symptoms and the misleading nature of anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the design in the ISCHEMIA trial is also evidenced by the availability of two separate flow-charts, to guide the invasive strategy in both imaging and non-imaging subgroups. The use of fractional flow reserve was strongly recommended [26,27], and most of the revascu-larization procedures were performed according to best practice evidence, with > 90% last-generation DES for PCI and internal mammary arteries for CABG [1]. The benefit of the invasive approach, albeit still not significant, was proportional to the extent of CAD.…”
Section: The Extent Of Revascularization In Multivessel Coronary Artementioning
confidence: 99%